ANALYSIS OF STUDENTS’ VOCABULARY MASTERY IN SECOND SEMESTER STUDENTS OF BUSINESS ENGLISH AND MANAGEMENT - Fariska Wulandari (IKIP PGRI Pontianak, 2019)
This research was conducted to find out the students’ vocabulary of second semester students of Business English and Management. The research was descriptive qualitative research. 65 students of second semester. Test, questionnaire, and observation sheet were used as the instrument of data collecting. The finding of this research was the students’ vocabulary ability was low that can be seen from the result of the test that the students’ mean score in vocabulary test is 50.8. Then, the results of questionnaire are 78.46 % students like learning vocabulary, 53.84 % students think that vocabulary ability is very important. It means that students have realized that vocabulary ability is essential. Although 53.84 % students think that vocabulary ability is very important, 0 % students think that their vocabulary ability is high and 52.30 % think that their vocabulary ability is medium. In addition, results of the observation while the students doing the test were the researcher found that some students still get confused of the test.Key words: vocabulary ability, descriptive analysis, vocabulary test, questionnaire, observation.